2015
DOI: 10.1111/hel.12205
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Viable Helicobacter pylori in Drinking Water Supplies by Cultural and Molecular Techniques

Abstract: Our results demonstrate for the first time that H. pylori can survive and be potentially infective in drinking water, showing that water distribution systems could be a potential route for H. pylori transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
21

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 32 publications
3
67
0
21
Order By: Relevance
“…E. coli O157:H7 is one of the most common pathogenic bacteria in water with a low infective dose, several researchers (Al‐Qadiri et al, ; Kerr et al, ) found that it was able to survive for long storage time under cold temperatures in bottled water without essential nutrients. Moreover, in many E. coli waterborne outbreaks, the detected numbers were less than 10 4 CFU/100 ml (Banihashemi, Van Dyke, & Huck, ; Li, Xin, & Li, ; Santiago, Moreno, & Ferrus, ). Therefore, the detection of E. coli O157:H7 at low concentration was quite necessary.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli O157:H7 is one of the most common pathogenic bacteria in water with a low infective dose, several researchers (Al‐Qadiri et al, ; Kerr et al, ) found that it was able to survive for long storage time under cold temperatures in bottled water without essential nutrients. Moreover, in many E. coli waterborne outbreaks, the detected numbers were less than 10 4 CFU/100 ml (Banihashemi, Van Dyke, & Huck, ; Li, Xin, & Li, ; Santiago, Moreno, & Ferrus, ). Therefore, the detection of E. coli O157:H7 at low concentration was quite necessary.…”
Section: Discussionmentioning
confidence: 99%
“…PMA-PCR was first reported to effectively exclude the signal of dead bacteria (Nocker et al, 2006; Josefsen et al, 2010). Later, this approach was adapted by many scientists to detect viable cells of various foodborne pathogens (Cawthorn and Witthuhn, 2008; Josefsen et al, 2010; Liang et al, 2011; van Frankenhuyzen et al, 2011; Banihashemi et al, 2012; Li and Chen, 2012, 2013; Mamlouk et al, 2012; Soejima et al, 2012; Dinu and Bach, 2013; Singh et al, 2013; Yang Y. et al, 2013; Ditommaso et al, 2015; Li et al, 2015; Santiago et al, 2015; Cattani et al, 2016). The majority of the studies demonstrated that PMA-PCR effectively suppressed the signal of DNA from the dead cells.…”
Section: Limitations Of the Pma Approach And The Remedies To Address mentioning
confidence: 99%
“…34 While it is plausible that water contaminated by H. pylori is a route for the transmission of H. pylori infection, the quantities of H. pylori reported to be in drinking water and thus the risk of infection from such sources remain poorly characterized. 37 Both studies had limited sample sizes (n = 87 and n = 24, respectively) and were conducted in a variety of locations. To our knowledge, only two studies have quantitatively measured H. pylori in municipal drinking water: one by our group in Lima, Peru, 26 and the other in Spain.…”
mentioning
confidence: 99%